MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE SQ3R PADA PEMBELAJARAN SEJARAH KELAS XII SMA NEGERI 1 TEMBILAHAN HULU - Wardiah (JURNAL RANDAI, 2021)
Low activity, student creativity in the learning process can result in the teaching and learning process being less than optimal so that the material presented is incomplete according to the expected completeness criteria. From the results of observations and discussions with the history subject teacher, information is obtained that the learning system has not fully involved students as the subject of learning consequently the final result to be achieved, namely individual and classical learning completeness with KKM (minimum completeness criteria) has not been achieved. One of the efforts made to improve the process and student learning outcomes, a learning method is used that makes it easier for students to compile and understand information or the content of the lesson text in increasing understanding of social studies subject matter so that learning outcomes are expected to increase, through the use of the SQ3R method. Based on the background of the problem, the formulation of the problem in this study is: "How are the students' learning outcomes increased through the SQ3R method in history learning for students of XII SMA Negeri 1 Tembilahan Hulu Indragiri Hilir? "The purpose of this study is to determine the activities of teachers and students as well as the improvement of student learning outcomes in history subjects through the SQ3R method for class XI SMAN 1 Kateman Indragiri Hilir. The conclusion of this study is that the student learning outcomes, before CAR the average daily test was 64.3, after the CAR based on the daily test cycle I increased to 81.8 and was included in the good category. In the second cycle of daily tests, it increased again to 92.8 and was included in the very good category. Thus, the use of the SQ3R method can improve student learning outcomes in history learning for class XII at SMAN 1 Tembilahan Hulu, Indragiri Hilir Regency